A Computerized Prescription Writing Program for Doctors - Brown, C. S.; Allen, S. I.; Songco, D. C. (Methods of Information in Medicine, 1985)
A computer-assisted system designed to write drug prescriptions and patient instructions has been in operation in a dermatologist’s office for two years. Almost all prescriptions are generated by the machine. Drug dosages, directions, and labeling phrases are retrieved from a diagnosis-oriented formulary of 300 drug products. A prescription template with preselected default options is displayed on a terminal screen where selection is made with the use of the video pointer. Typing skill is not required, as a detailed prescription can be produced from the use of only five function keys. Prescriptions and sets of relevant instructions for the patient are computer-printed. Therapy summaries for the medical record also are automatically composed and printed.
Keywords: Microcomputer System; Prescription Writing; Office Practice; Five-Key Finger-pad; Drug Formulary